Editorial (GnosisWisdom, 2022)
The Journal of Scientific and Technological Research and Innovation GnosisWisdom, presents Vol.2, No 3 (2022) is a peer-reviewed publication managed through the Open Journal System. Its objective is worldwide dissemination, in its electronic version, it publishes original works on multidisciplinary topics that retain a character of originality, usefulness, scientific and technological relevance; that provide new knowledge on theoretical or practical aspects in the different areas of knowledge.